Pre-operative carbohydrate loading prior to elective caesarean delivery: a randomised controlled trial. (February 2021) - Clark, A.; Litchfield, K.; Hannah, S.; Love, C.; Slade, K.; Lake, K.; Agaram, R.
Highlights: Pre-operative carbohydrate drinks can improve outcomes following major surgery. Little evidence exists to support use prior to elective caesarean delivery. Carbohydrate drinks reduced pre-operative urinary ketones from 61% to 18%. Use of carbohydrate drinks did not affect length of hospital stay. Abstract: Introduction: Women undergoing elective caesarean deliveries are fasted for long periods prior to surgery and can become catabolic. The use of pre-operative carbohydrate drinks to optimise patients ahead of major surgery is now well established. However, evidence to support this in women undergoing elective caesarean delivery is limited. Methods: We conducted a single-blind randomised control trial to study the effect of carbohydrate preloading on the presence of urinary ketones in mothers undergoing elective caesarean deliveries compared with standard care, fasting from midnight the night before surgery with free clear fluids until two hours prior to surgery. Results: Two-hundred-and-nine patients were allocated to either standard care (n=104) or pre-operative carbohydrate drinks (n=105) prior to elective caesarean section. Twenty-five were excluded from the analysis, leaving 184 (n=90; n=94). The incidence of urinary ketones immediately prior to surgery was lower in the carbohydrate group, 18.1% compared with 61.1% in the standard care group (P<0.001). Relative risk (95% CI) 3.33 (2.12 to 5.26), with a number needed-to-treat of three to prevent urinary ketosis in one woman. There were no major adverse events. Conclusion: The results of this study support the introduction of carbohydrate drinks ahead of caesarean delivery to offset the effects of pre-operative fasting. However, the results may not be generalisable to all maternity units due to differences in fasting protocols.